Development of PSMA-1007-related series of 18F-labeled Glu-Ureido-type PSMA inhibitors - Cardinale, Jens; Roscher, Mareike; Schäfer, Martin; Geerlings, Max; Benes̆ová, Martina; Bauder-Wüst, Ulrike; Remde, Yvonne; Eder, Matthias; Nováková, Zora; Motlová, Lucia; Barinka, Cyril; Giesel, Frederik L.; et al. (Journal of medicinal chemistry, 2020)
In recent years, a number of drugs targeting the prostate-specific membrane antigen (PSMA) have become important tools in the diagnosis and treatment of prostate cancer. In the present work, we report on the synthesis and preclinical evaluation of a series of 18F-labeled PSMA ligands for diagnostic application based on the theragnostic ligand PSMA-617. By applying modifications to the linker structure, insight into the structure-activity relationship could be gained, highlighting the importance of hydrophilicity and stereoselectivity on interaction with PSMA and hence the biodistribution. Selected compounds were co-crystallized with the PSMA protein and analyzed by X-rays with mixed results. Among these, PSMA-1007 (compound 5) showed the best interaction with the PSMA protein. The respective radiotracer [18F]PSMA-1007 was translated into the clinic and is, in the meantime, subject of advanced clinical trials.
Gesehen am 03.02.2021